Preparation and characterization of core-shell structured LiFePO4/C composite using a novel carbon source for lithium-ion battery cathode. (March 2017) - Huang, Zan; Luo, Peifang; Wang, Daxiang
Abstract: Core-shell structured LiFePO4 /C1 cathode material is synthesized via a rapid microwave irradiation route using ethylene diamine tetraacetic acid (EDTA) as the novel carbon source. XRD results reveal that all the patterns can be indexed as the olivine-type structured LiFePO4 with the space group of Pnma . TEM images show that the obtained carbon is an amorphous layer with a thickness of about 3–4 nm. When the LiFePO4 /C1 used as cathode material for lithium-ion battery, it delivers an initial discharge capacity of 163.1 mAh g −1 at 0.1 C which is about 96% of the theoretical capacity. Moreover, it also shows excellent rate performance and good cycle stability due to the enhanced electronic conductivity as proved by the electrochemical impedance spectroscopy (EIS). Thus, this carbon decorated LiFePO4 composite synthesized via the rapid microwave irradiation method is a promising cathode material for high-performance lithium-ion battery. Graphical abstract: Highlights: Carbon-coated LiFePO4 was synthesized via a rapid microwave irradiation route. The EDTA was used as the novel carbon source for the first time. The as-fabricated cathode exhibited superior rate capability and cycling stability.